From Flock to Fortune: Empowering Rural Entrepreneurship through Sheep Farming in the Uttarakhand Himalayas - Uniyal, Sona (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
In high-altitude regions of Uttarakhand, India, traditional sheep rearing has long served subsistence needs for pastoral communities. However, this vital livelihood remains under-commercialized despite its potential to support resilient rural entrepreneurship. This review critically examines how sheep-based enterprises in the Himalayan region particularly in districts like Tehri Garhwal and Uttarkashi can be transformed into sustainable micro-enterprises that generate income, empower women, youth and strengthen hill economies. Using a mixed-methods approach the paper synthesizes secondary data from peer-reviewed studies, government reports (e.g., 2019 Livestock Census) and policy schemes such as the National Livestock Mission (NLM), “Goat Valley” initiative, and ICAR-MANAGE interventions. Case studies from Ghansali and Gangi villages are used to illustrate implementation models. The findings highlight that sheep offer multiple income streams wool, meat, and manure while thriving on marginal land with minimal input. Breed improvement initiatives, financial subsidies and cooperative models (SHGs, FPOs) have begun converting traditional flocks into commercial units. The Ghansali Merino breeding project exemplifies how targeted government support can raise fleece quality and income. Nevertheless, barriers such as fodder scarcity, weak veterinary services and limited entrepreneurial training hinder progress. The study argues for an integrated support ecosystem comprising breed access, digital extension, credit mechanisms and market linkages to transition from subsistence to entrepreneurship. By aligning traditional knowledge with targeted innovations and enabling policy, sheep farming in Uttarakhand can evolve into a scalable, eco-friendly model for inclusive rural development. The paper concludes with policy recommendations for mainstreaming small ruminant enterprises into India’s broader rural transformation agenda.